Implementasi Teknologi Smokeless Burn Barrel Sebagai Alternatif Pengelolaan Sampah - Maulidia, Syafa Zaudan; Faoziyah, Laeli; Yahya, Sevi Efrian; Ayu, Kamila Sekar; Wijaya, Mohammad Krisna Hadi; Farizki, Muhammad Ivan; Abduhaq, Nabil; Advani, Muchlis Adi; Herdanto, Anyeu Minda; Abdullah, Rigia Sabil; Sunardi, Sunardi (Universitas Muhammadiyah Yogyakarta, 2025)
Open burning of waste is still commonly practiced, especially in areas without adequate waste management systems, leading to air pollution and adverse effects on health and the environment. Pollutants such as carbon monoxide (CO), nitrogen oxides (NOx), and fine particulate matter (PM2.5) contribute to respiratory issues and climate change. This program aims to introduce the Smokeless Burn Barrel technology as a solution to reduce smoke emissions from household waste burning. The activity was conducted in RW 07, Warungboto, DIY, through socialization, training on the construction of the device, and trials of its use. The methods used include education on the impacts of air pollution, technical demonstrations, and evaluation of the device's effectiveness. The trial results showed that the Smokeless Burn Barrel improved combustion efficiency, reduced ash residue by 66.7%, increased combustion temperature by 26.8%, and saved fuel by up to 50%. Smoke emissions were also significantly lower, reducing the negative impact on the environment and public health. The outcome of this activity was an increase in public awareness and behavior change in waste management. Residents have begun to switch to more environmentally friendly burning methods and have shown enthusiasm in independently applying this technology. Some residents even initiated the collective construction and use of Smokeless Burn Barrels at the neighborhood level (RT). This program has contributed to reducing air pollution and raising awareness and independence in the community for more sustainable waste management